Peran Guru dalam Menghadapi Perilaku Aktif dan Gejala Tantrum pada Anak Usia Dini - Hilda Zahra Lubis; Adinda Hasri (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Early Childhood Education (PAUD) is the main foundation in character building, but in practice, challenges such as excessive active behavior and tantrums are often found. This study aims to identify children's behavior at school, understand the causes of social-emotional problems, and relate them to relevant developmental theories. The research method used was descriptive qualitative with data collection techniques through direct observation and field notes at the IT Padepokan Iqra Kindergarten. The results of the observation showed that boys tended to be more physically active due to their dominant gross motor development, while tantrums were influenced by separation anxiety. In conclusion, these behaviors are a natural part of child development that requires activity-based learning strategies, an emotional coaching approach, and intensive collaboration between teachers and parents. A deep understanding of the individual characteristics of children is the key to success in managing a heterogeneous classroom.